Forearm pronation efficiency in A.L. 288‐1 (Australopithecus afarensis) and MH2 (Australopithecus sediba): Insights into their locomotor and manipulative habits. Issue 4 (26th September 2017) - Ibáñez‐Gimeno, Pere; Manyosa, Joan; Galtés, Ignasi; Jordana, Xavier; Moyà‐Solà, Salvador; Malgosa, Assumpció
Abstract: Objectives: The locomotor and manipulative abilities of australopithecines are highly debated in the paleoanthropological context. Australopithecus afarensis and Australopithecus sediba likely engaged in arboreal locomotion and, especially the latter, in certain activities implying manipulation. Nevertheless, their degree of arboreality and the relevance of their manipulative skills remain unclear. Here we calculate the pronation efficiency of the forearm ( E rot ) in these taxa to explore their arboreal and manipulative capabilities using a biomechanical approach. Materials and methods: Three‐dimensional humeral images and upper limb measurements of A.L. 288‐1 ( Au. afarensis ) and MH2 ( Au. sediba ) were used to calculate E rot using a previously described biomechanical model. Results: Maximal E rot in elbow flexion occurs in a rather supinated position of the forearm in Au. afarensis, similarly to Pan troglodytes . In elbow extension, maximal E rot in this fossil taxon occurs in the same forearm position as in Pongo spp. In Au. sediba the forearm positions where E rot is maximal are largely coincident with those for Hylobatidae. Conclusions: The pattern in Au. afarensis suggests relevant arboreal capabilities, which would include vertical climbing, although it is suggestive of poorer manipulative skills than in modern humans. The similarity between Au. sediba and Hylobatidae is difficult to interpret, but the differences between Au. sediba and Au. afarensis suggest that the capacity to rotate the forearm followed different evolutionary processes in these australopithecine species. Although functional inferences from the upper limb are complex, the observed differences between both taxa point to the existence of two distinct anatomical models.